Bacitracin Methylene Disalicylate (BMD) Treatment Affects Spleen Proteome in Broiler Chicks Infected with Salmonella enteritidis - Adedeji Adetunji; Theresa Casey; Uma K. Aryal; Tunde Ogundare; Jackeline Franco; Yewande Fasina (MDPI AG, 2024)
Bacitracin Methylene Disalicylate (BMD), as a feed additive to poultry diets, enhances digestion, prevents Salmonella enteritidis (SE) colonization, and treats current infections. The objective of this study was to utilize a quantitative proteomic approach to determine the effect of BMD feed additive on broiler chickens challenged with SE in the spleen proteome. At 1 d of age, chicks were randomly allocated into four groups: control with and without SE challenge (CON, n = 60; CON-SE, n = 60), BMD with and without SE challenge (BMD, n = 60; BMD-SE, n = 60). Birds in the CON-SE and BMD-SE treatment were administered SE inoculum by oral gavage. On day three and day seven post-gavage, the spleen was collected aseptically from birds in each treatment group (CON, n = 4/day; CON-SE, n = 4/day; BMD, n = 4/day; BMD-SE, n = 4/day). Proteomic analysis by liquid chromatography-tandem mass spectrometry (LC-MS/MS) showed an increased abundance of 115 proteins and decreased of 77 due to the BMD. Proteins that decreased in abundance were enriched for fibrinogen complex and extracellular space, whereas proteins that increased in abundance were enriched for proteasome-mediated ubiquitin-dependent protein catabolic process and mitochondrion. Analysis of the interaction between BMD and the Salmonella challenge found 230 differentially abundant proteins including proteins associated with RNA binding, spliceosome, protein transport, and cell adhesion among the upregulated proteins, and those associated with protein folding, carbon metabolism, biosynthesis of nucleotide sugars, response to oxidative stress, positive regulation of NIK/NF-kappaB signaling, and inflammatory response among the downregulated proteins. The impact of BMD treatment on spleen proteome indicates an anti-apoptotic effect. BMD also modified the response of the spleen to the SE challenge with a marked decrease in proteins that prompt cytokine synthesis and an increase in proteins involved in the selective removal of unfolded proteins.